Market Development Strategies for Florida Fresh Sweet Corn: Findings from a Consumer Survey, 2001 - Tom Stevens; Robert Degner; Kimberly Morgan; Chris deBodisco; Lisa House (EDIS)
From 1998 through 2001, the Fresh Supersweet Corn Council promoted fresh sweet corn directly to consumers through a third-party communications agency. In 2001, the Council contracted with the Florida Agricultural Market Research Center at the Institute of Food and Agricultural Sciences to conduct a consumer survey to evaluate existing and potential impediments to future market growth for both wholesale and retail stages and to make recommendations for specific marketing strategies that could increase Council members' profitability. This document briefly reviews the procedures and findings of that analysis. This is EDIS document FE377, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2003.